2011
DOI: 10.1104/pp.111.173336
|View full text |Cite
|
Sign up to set email alerts
|

The Pea SAD Short-Chain Dehydrogenase/Reductase: Quinone Reduction, Tissue Distribution, and Heterologous Expression    

Abstract: The pea (Pisum sativum) tetrameric short-chain alcohol dehydrogenase-like protein (SAD) family consists of at least three highly similar members (SAD-A, -B, and -C). According to mRNA data, environmental stimuli induce SAD expression. The aim of this study was to characterize the SAD proteins by examining their catalytic function, distribution in pea, and induction in different tissues. In enzyme activity assays using a range of potential substrates, the SAD-C enzyme was shown to reduce one-or two-ring-membere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…For the former, SDR is often expressed at certain stages during development and in specific tissues, for example, tuber, root, glandular hair of leaves, flower and fruit (Okamoto et al, 2011;Chen et al, 2011). As for the latter, the studies have shown that the tetramer SAD of pea has at least three similar family members (SAD-A, SAD-B and SAD-C), and mRNA expression indicated that SAD expression can be induced by the environment (Scherbak et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For the former, SDR is often expressed at certain stages during development and in specific tissues, for example, tuber, root, glandular hair of leaves, flower and fruit (Okamoto et al, 2011;Chen et al, 2011). As for the latter, the studies have shown that the tetramer SAD of pea has at least three similar family members (SAD-A, SAD-B and SAD-C), and mRNA expression indicated that SAD expression can be induced by the environment (Scherbak et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is no indication that short-chain dehydrogenases participate in the biosynthesis of gibberellins (Sponsel and Hidden, 2004) but SlscADH1 belongs to a family comprising a number of genes identified as involved in plant growth regulation, notably AtABA2 (AT1G52340.1) that catalyzes the conversion of xanthoxin into ABA-aldehyde (Cheng et al, 2002;González-Guzmán et al, 2002) and the grasses flower feminization protein TASSELSEED2 (DeLong et al, 1993;Malcomber and Kellogg, 2006) that displays 3␤/17␤-hydroxysteroid dehydrogenase and carbonyl/quinone reductase activities (Wu et al, 2007). Alternatively, other members of the SDR110C family intervene in different branches of secondary metabolism, such as rice momilactone A synthase (diterpenoid phytoalexin synthesis, Shimura et al, 2007), secoisolariciresinol dehydrogenase (lignan synthesis, Xia et al, 2001) or pea short-chain alcohol dehydrogenase-like protein (quinone reduction, Scherbak et al, 2011). Thus, the possibility that the dwarf phenotype arises as a consequence of the accumulation of a toxic precursor cannot be ruled out.…”
Section: Effects Of Constitutive and Fruit-specific Down-regulation Omentioning
confidence: 99%
“…A detailed presentation of the SDR110C family (Fig. 2B) shows that it encompasses several dehydrogenases known to participate in plant secondary metabolism or hormone biosynthesis (for review, see Tonfack et al, 2011): Forsythia intermedia secoisolariciresinol dehydrogenase (Xia et al, 2001), rice momilactone A synthase (Shimura et al, 2007), ABA2 xanthoxin dehydrogenase (Cheng et al, 2002;González-Guzmán et al, 2002), spearmint isopiperitenol dehydrogenase (Ringer et al, 2005), pea short-chain alcohol dehydrogenaselike protein (P.s.-SAD-A, Scherbak et al, 2011). In addition to AtABA2, other members of the SDR110C were reported for their involvement in plant development despite a lack of information concerning the reaction catalyzed by the enzyme.…”
Section: Analysis Of the Slscadh1 Sequence And Phylogenymentioning
confidence: 99%